AN ASSESSMENT OF UNITED KINGDOM’S MEMBERSHIP TO EUROPEAN UNION DURING BREXIT PERIOD - P. S., Balasubramanya (ShodhKosh: Journal of Visual and Performing Arts, 2022)
This paper mainly explains about United Kingdom's membership to European Union during Brexit period. Regarding United Kingdom's membership to European Union, many studies had conducted in different parts of the World. But all these studies give a partial or one-sided views about United Kingdom's membership to European Union. There were different approaches had developed to understand the complete picture of the European Union’s origin, development and United Kingdom's membership. The study analyzes the reasons and the cause for United Kingdom's membership to the European Union during Brexit period. The whole study can be broadly divided into three stages. In the first stage, the study includes the basic ideas, theories and different models to know about the reasons behind the European Union’s formation. In the Second stage, the study includes the influence of European political, economic, social conditions after the Second World War in forming the European Union. In the third stage, the study involves the reasons behind United Kingdom's membership to European Union during Brexit period.